POTENSI ANGKAK (RED YEAST RICE) SEBAGAI PENCEGAH SINDROM METABOLIK - Ambarwati Savira Putri; Yasmin Alifya Nidaankhofiya; Saryono (Unit Penelitian dan Pengabdian Masyarakat Politeknik Banjarnegara, 2021)
Metabolic syndrome is a complex metabolic disorders that occur as a result of factors associated with the risk of cardiovascular problems. These factors are atherosclerosis, dyslipidemia, diabetes, hypertension, and obesity. From a treatment perspective, there is no multifunctional drug that can cure those factors simultaneously. Therefore, from a preventive perspective, adjuvant drugs are necessary to block the development of metabolic disease. Red yeast rice is a product that produced through fermentation of rice (Oryza sativa L.) with Monascus purpureus. The fermentation process produces rice with red pigment, a distinctive taste, and contains bioactive components. One of its component is monacolin-K that chemically identical to lovastatin. Red yeast rice’s bioactive components are the basis for the use of red yeast rice as a potential prevention of the factors that trigger metabolic syndrome. This systematic review aims to analyze red yeast rice as a food ingredient that can prevent metabolic syndrome. Articles are obtained from electronic databases, such as PubMed and Google Scholar, that published from 2011 to 2021. Keywords used are red red yeast rice, metabolic syndrome, atherosclerosis, dyslipidemia, diabetes, hypertension, and obesity. The results of 5 selected articles indicate that red yeast rice is potential in the prevention of metabolic syndrome, because monacolin-K and other bioactive components that contained in red yeast rice are able to reduce the factors of metabolic syndrome. Monacolin K is an inhibitor of the hydroxymethylglutaryl-CoA (HMG-CoA) reductase, which reduces the production of LDL-Cholesterol in the liver. Meanwhile, the other bioactive components can inhibit α-glucosidase enzyme that causes the catalization of complex carbohydrates becomes slower and glucose levels in the blood tend to be stable.